The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1101/2023.02.09.527810
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combining organotypic tissue culture with multi-color fluorescence light-sheet microscopy (OTCxLSFM) – a novel tool to study glioma invasion/migration

Abstract: Glioblastoma is a very aggressive tumor and represents the most common primary brain malignancy. Key characteristics include its high resistance against conventional treatments, such as radio- and chemotherapy and its diffuse tissue infiltration, preventing complete surgical resection. The analysis of migration and invasion processes in a physiological microenvironment allows for enhanced understanding of these processes and can lead to improved therapeutic approaches. Here, we combine two state-of-the-art tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Irradiated tumors appeared similarly invasive to solvent-treated tumors, but with decreased sizes. To confirm this observation we applied an imaging technique combining OTC culture with light sheet fluorescence microscopy (LSFM) called OTCxLSFM (Haydo et al, 2023) to measure the tumors and its particular single cell invasion in a 3D manner and display it in 90° angles (Figure 5D). This advanced microscopy approach confirmed that DMSO-treated tumors display diffuse 3D infiltration and spreading of cells into the surrounding brain tissue.…”
Section: Curcusone D a Brat1 Inhibitor Decreases The Pro-migratory/in...mentioning
confidence: 95%
See 4 more Smart Citations
“…Irradiated tumors appeared similarly invasive to solvent-treated tumors, but with decreased sizes. To confirm this observation we applied an imaging technique combining OTC culture with light sheet fluorescence microscopy (LSFM) called OTCxLSFM (Haydo et al, 2023) to measure the tumors and its particular single cell invasion in a 3D manner and display it in 90° angles (Figure 5D). This advanced microscopy approach confirmed that DMSO-treated tumors display diffuse 3D infiltration and spreading of cells into the surrounding brain tissue.…”
Section: Curcusone D a Brat1 Inhibitor Decreases The Pro-migratory/in...mentioning
confidence: 95%
“…Figure 5A), similarly as genetic BRAT1-depletion. Likewise, migration of the GSC line GS-5 (Günther et al, 2008) on laminincoated plates was inhibited by CurD using a sphere migration assay (Haydo et al, 2023) (Suppl. Figure 5B).…”
Section: Curcusone D a Brat1 Inhibitor Decreases The Pro-migratory/in...mentioning
confidence: 99%
See 3 more Smart Citations